1975
DOI: 10.1121/1.380717
|View full text |Cite
|
Sign up to set email alerts
|

Monaural localization of low-pass noise bands in the horizontal plane

Abstract: Monaural localization of low-pass noise positioned in the horizontal plane on the side of the unoccluded ear was investigated. Listeners showed no localizing ability until the upper cutoff frequency of the noise was advanced to 5.0 kHz. Performance proficiency increased progressively with the inclusion of still higher audio frequencies. Consonant with the behavioral data were the results of sound spectrum measurements performed on a head–pinna model. The spectral composition of a broad-band noise positioned at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Monaural cues (spectral cues and head shadow effect) are involved in the localization of sounds when one ear is obstructed, or in unilaterally deaf subjects [37]. However, spectral cues also contribute to BSL, particularly for vertical and front-back discrimination [38], but also for azimuth localization [39,40]. Moreover, some authors suggest that spectral cues based on head-related transfer function templates are sensitive to experience [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Monaural cues (spectral cues and head shadow effect) are involved in the localization of sounds when one ear is obstructed, or in unilaterally deaf subjects [37]. However, spectral cues also contribute to BSL, particularly for vertical and front-back discrimination [38], but also for azimuth localization [39,40]. Moreover, some authors suggest that spectral cues based on head-related transfer function templates are sensitive to experience [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we do not know whether lowfrequency sounds-<4.0 kHz-when added to sounds of higher frequencies improve performance. The Belendiuk and Butler (1975) experiment only investigated the performances as the high-frequency cutoff of a low-pass noise was increased progressively. Nor, as mentioned earlier, do we know whether frequencies >11.0 kHz contribute toward proficiency in monaural localization in the HP.…”
Section: Methodsmentioning
confidence: 99%
“…The stimulus must be complex; judgments of the location of sinusoids in the monaural localization task do not correspond to their actual location (Angell & Fite, 1901;Butler, 1971). Also, the higher audio frequencies->5.0 kHz -must be included in the sound before a subject can attain maximal accuracy (Belendiuk & Butler, 1975). But there exists at least one set of stimulus conditions which fails to affect the MSP and the monaural HP localization tasks similarly.…”
mentioning
confidence: 99%
“…A number of studies demonstrated that people listening with just one ear can localize sound sources in the horizontal plane although such localization accuracy is much poorer than with two ears and all localization judgments are shifted toward the active ear (Belendiuk and Butler, 1975;Butler 1987;Butler and Flannery, 1980;Jin et al, 2004;Morimoto, 2001;Oldfield and Parker, 1984a;Van Wanrooij and Van Opstal, 2004). Such localization ability is proof that horizontal localization can, to some degree, be facilitated by monaural cues.…”
Section: Monaural Cuesmentioning
confidence: 99%